TFF2, a novel serum diagnostic biomarker for early pancreatic cancer - Wu, Xiangyu; Huang, Xiuhong (Frontiers in Oncology, 2025)
BackgroundEarly detection and intervention are critical for improving the prognosis of pancreatic cancer (PC), but effective screening tests remain unavailable.MethodsA retrospective analysis was conducted on 92 PC cases, 50 benign pancreatic disease cases, 92 periampullary adenocarcinoma cases, and 92 healthy controls from September 2020 to September 2024 at Handan Central Hospital. Serum levels of CA199 and CEA were measured, and their diagnostic performance was evaluated by the area under the receiver operating characteristic (ROC) curve (AUC). Additionally, publicly available cancer genome datasets were analyzed to identify specific serum biomarkers for early PC, and clinical serum samples were collected to validate their expression and diagnostic utility.ResultsCA199 and CEA effectively differentiated PC from benign pancreatic diseases and normal controls. However, they demonstrated limited value for distinguishing PC and periampullary carcinoma, with AUC values of 0.571 and 0.604, respectively. Trefoil factor 2 (TFF2), a gene encoding exocrine protein, was found to be specifically upregulated in pancreatic intraepithelial neoplasia and PC, with no significant expression observed in benign pancreatic diseases, cholangiocarcinoma, or hepatocellular carcinoma. Importantly, serum TFF2 levels were significantly elevated in the PC group, with AUC values of 0.947 for distinguishing PC from normal controls and 0.856 for differentiating it from periampullary adenocarcinoma, outperforming CA199 and CEA. The combination of TFF2 enhanced accuracy of CA199 and CEA to discriminate PC from periampullary adenocarcinoma.ConclusionsSerum TFF2 is a promising test for early screening of PC and may enhance diagnostic performance when combined with CA199 and CEA.